2022
DOI: 10.1088/1361-6595/ac5cd4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted combustion with nanosecond discharges. I: Discharge effects characterization in the burnt gases of a lean flame

Abstract: The prediction of a flame response to plasma assistance requires extensive knowledge of discharge-induced plasma kinetics. Detailed studies of nanosecond discharges are common in N2/O2 and fresh combustible mixtures but are still lacking in burnt gases. To fill this gap, we define a combustion reference test case and investigate the effects of Nanosecond Repetitively Pulsed (NRP) discharges placed in the recirculation zone of a lean (Φ = 0.8) CH4-air bluff-body stabilized flame at atmospheric pressure. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 70 publications
(164 reference statements)
2
29
0
Order By: Relevance
“…According to [19], the fraction of energy α responsible of the ultra-fast heating and the ultra-fast dissociation of species when NRP discharges are applied in lean burnt gases is similar to what was obtained for NRP discharges in pure air [12]. The fraction of energy that goes into ultra-fast heating (α -η) is also the same and is equal to 20%.…”
Section: Nanoseconds Pulsed Discharges Modelsupporting
confidence: 61%
See 1 more Smart Citation
“…According to [19], the fraction of energy α responsible of the ultra-fast heating and the ultra-fast dissociation of species when NRP discharges are applied in lean burnt gases is similar to what was obtained for NRP discharges in pure air [12]. The fraction of energy that goes into ultra-fast heating (α -η) is also the same and is equal to 20%.…”
Section: Nanoseconds Pulsed Discharges Modelsupporting
confidence: 61%
“…by dissociative quenching with O2 molecules leads leads to an ultra-fast increase of gas temperature and O2 dissociation into atomic oxygen [12].The Relaxation of vibrational states of N2 occurs on a much longer times scales, milliseconds scales, and results in slow gas heating. The recent measurement performed by Minesi et al [19] showed that when applied in a mixture of lean flame burnt gases the NRP discharges induce similar effects.…”
Section: Nanoseconds Pulsed Discharges Modelmentioning
confidence: 94%
“…572 In addition to the concentrations of the main and intermediate combustion species, including excited and charged particles, the electric field and electron density distribution should be determined as a function of the fuel−oxidizer−bath gas system and of the relevant discharge parameters, on the time scales of the related processes. 570,571,574 Current research in plasma-assisted combustion is devoted to study ignition, 575−580 flame stabilization and combustion enhancement, 578,581−586 kinetics and mechanism development, 575,579−581,587−590 process visualization, 576,577,582,591,592 species diagnostics, 575,582,584−586,588−590,593−597 electric field and/or electron density measurements, 586,596,598 and numerical simulation, 575,[577][578][579][580]584,591,592,597 using different types of plasma generation, e.g., with repetitively pulsed nanosecond, [576][577][578]581,585,586,[591][592][593]595,599 dielectric barrier discharge, 577,579,588,590,594,596,597 gliding arc, …”
Section: Combustion and Plasma Activationmentioning
confidence: 99%
“…570,571,574 Current research in plasma-assisted combustion is devoted to study ignition, 575−580 flame stabilization and combustion enhancement, 578,581−586 kinetics and mechanism development, 575,579−581,587−590 process visualization, 576,577,582,591,592 species diagnostics, 575,582,584−586,588−590,593−597 electric field and/or electron density measurements, 586,596,598 and numerical simulation, 575,[577][578][579][580]584,591,592,597 using different types of plasma generation, e.g., with repetitively pulsed nanosecond, [576][577][578]581,585,586,[591][592][593]595,599 dielectric barrier discharge, 577,579,588,590,594,596,597 gliding arc, 582,583 and microwave 584 activation. Fuels include hydrogen, 577,597,…”
Section: Combustion and Plasma Activationmentioning
confidence: 99%
See 1 more Smart Citation